Endokrin Aciller - Gökdemir, Gül Şahika; Yucal, Aykut; Çeliktürk, Eray; Salt, Ömer; Özbilen, Mehmet Selim; Bozatlı, Satuk Buğra Han; Ünaldı, Mehmet; Sayhan, Mustafa Burak; Giray, Tufan Akın; Aksoy, Gökhan; Aksoy, Zeynep; Çakmakçı, Aktuğ; et al. (Academician Publishing Book DOI Portal, 2023)
-